2017
DOI: 10.1002/gj.2921
|View full text |Cite
|
Sign up to set email alerts
|

The geophysical identification, characteristics, and petroliferous significance of sublacustrine fan deposits in the second member of Dongying Formation in Liaozhong Depression, Bohai Bay Basin

Abstract: Large sublacustrine fan deposits have been identified within the lacustrine successions of the second member of the Palaeogene Dongying Formation in the Liaozhong Depression. In this study, by using comprehensive and detailed analyses of the borehole lithology, limited cores, wireline logs, and seismic facies, 4 types of sublacustrine fan deposits were identified and characterized. Then, an integrated depositional model was established based on the above investigations. The result indicates that the geophysica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…It has been suggested the T 2 surface (ca. 25 Ma) records an important turning point for the basin evolution (Huang et al, 2014; Li, Zhao, Dai, Zhou, et al, 2012; Ren et al, 2010; Xia, Liu, et al, 2018); on the one hand, the rifting ceased and the dip‐slip faulting weakened greatly; on the other hand, the stress field changed to E‐W compression instead of NW stretching of the rifting stage. Previous studies suggested that during the Neogene‐Quaternary, the basin was in the context of long‐term thermal subsidence with E‐W compression, several episodic positive tectonic inversions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested the T 2 surface (ca. 25 Ma) records an important turning point for the basin evolution (Huang et al, 2014; Li, Zhao, Dai, Zhou, et al, 2012; Ren et al, 2010; Xia, Liu, et al, 2018); on the one hand, the rifting ceased and the dip‐slip faulting weakened greatly; on the other hand, the stress field changed to E‐W compression instead of NW stretching of the rifting stage. Previous studies suggested that during the Neogene‐Quaternary, the basin was in the context of long‐term thermal subsidence with E‐W compression, several episodic positive tectonic inversions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors referred the BBB as a pull‐apart basin dementated by widely distributed strike‐slip faults, whereas others proposed the basin as a Cenozoic rift basin but significantly deformed by strike‐slipping (Chen & Zhao, 1996; Hu, O'Sullivan, Raza, & Kohn, 2001; Lin, Zheng, Ren, Liu, & Qiu, 2003; Yu et al, 2020). The latter has been prevailing in recent studies (Xia et al, 2018; Yixin et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…During this period, a series of grabens and half-grabens were well developed along major NW-and NEtrending fault sets (Yang & Xu, 2004). The syn-rift sediments (65-24.6 Ma) unconformably overlying the Mesozoic basement, from bottom to top, mainly comprises the Paleogene Kongdian (Ek), Shahejie (Es), and Dongying formations (Ed) that were deposited primarily in fluvial-lacustrine environments (Jiu et al, 2013;Li, Liu, Niu, & Guo, 2014;Xia et al, 2017). When entered the post-rift period (24.6 Ma to the present), the entire basin experienced thermal subsidence without intensive tectonism (Hao, Zhou, Zhu, Zou, & Yang, 2010;Li et al, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…In recent years, the researches on extensional process, associated mechanism and significances of petroliferous basins have become hot topics for sedimentary geology and petroliferous basin analysis at home and abroad (Hsiao, Graham, & Tilander, 2004, 2010; Ren, Tamaki, & Li, 2002; Yu & Koyi, 2016; Zhang, Wu, Li, Xiao, & Qi, 2017; Zhao et al, 2016; Zhu et al, 2015; Zhu, Jiang, Zhang, & Chen, 2012; Zhu, Liu, Zhang, Gurnis, & Ma, 2021). Liaodong Bay, which is situated in northeastern Bohai Bay Basin, as a key and potential area of hydrocarbon reserves, has been paid wide attentions by scholars and oil industry (Xia et al, 2018, 2018; Xia, Lin, Wu, & Du, 2022; Zhu et al, 2015; Zhu et al, 2021). The scholars have conducted numerous researches on tectonics, sequence stratigraphy, sedimentology, reservoir mechanism, which have achieved effective and fruitful results (Qi, Li, Yu, & Yu, 2013; Qi & Yang, 2010; Ren et al, 2002; Xia et al, 2022; Xia, Lin, et al, 2018; Xia, Liu, et al, 2018; Xu et al, 2008; Xu, Xu, Qiu, Lai, & Zhou, 2005; Yu & Koyi, 2016; Zhu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Liaodong Bay, which is situated in northeastern Bohai Bay Basin, as a key and potential area of hydrocarbon reserves, has been paid wide attentions by scholars and oil industry (Xia et al, 2018, 2018; Xia, Lin, Wu, & Du, 2022; Zhu et al, 2015; Zhu et al, 2021). The scholars have conducted numerous researches on tectonics, sequence stratigraphy, sedimentology, reservoir mechanism, which have achieved effective and fruitful results (Qi, Li, Yu, & Yu, 2013; Qi & Yang, 2010; Ren et al, 2002; Xia et al, 2022; Xia, Lin, et al, 2018; Xia, Liu, et al, 2018; Xu et al, 2008; Xu, Xu, Qiu, Lai, & Zhou, 2005; Yu & Koyi, 2016; Zhu et al, 2015). Extensional deformation, as an important indicator that can reflect structural characteristics and analyse geometric structure of sedimentary basins, has been used to carry out researches in different regions of Bohai Bay Basin (Dong, Qi, Yang, & Yuan, 2013; Hsiao et al, 2004, 2010; Qi, Zhou, & Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%